PERBANDINGAN OPTIMASI QUERY DENGAN VIEW DAN INDEXED VIEW - Kristina Kristina; Wasino Wasino; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Processing of complex queries involving join operation on large database will require long response time, particularly if the query returns large amounts of data. Therefore, it is necessary to do query optimization. View can be an effective tool to simplify a complex query. However, using view which returns large result sets can lead to bad performance. SQL Server has the ability to make a special kind of view called indexed view. Indexed view or also known as materialized view is a view that has a unique clustered index. When unique clustered index created on the view, the view results will be stored in the database. Query performance can be improved significantly by creating an indexed view which involves a complex process with a large amounts of data, such as aggregation and join.The research aims to prove performance benefits resulting from query optimization using indexed view. The experiments were conducted by testing and measuring response time for three types of query then compare the results. Queries that will be compared are query with view and query with indexed view. Experimental results proved that indexed view perform very well by improving response time when processing the query as compared to views.